REFLECTION OF METHODOLOGIES OF EDUCATIONAL RESEARCH: DOES ACTION RESEARCH EXPERIENCED BY THE STUDENTS AFFECT LEARNING DEVELOPMENT AND SHIFTED MINDSET ON RESEARCH OF EDUCATION? - Halim, Abdul; Chang, Wei-Shan (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2021)
Abstract: This paper reports reflections of one of the courses I took in this semester namely Methodologies of Educational Research. To construct this paper, I used qualitative biographical-reflective method which is aligned with interpretive paradigm of narrative inquiry research methodology to describe my own experience in the learning process. The data I used were the postings from Zuvio mobile application designed for advising learning process with online platform and personal experience from reflective process of the course. I analyzed the data with three-stage qualitative data analysis: data reduction, data display, and conclusion. The findings report that the classroom undergone with classroom action research has successfully overcome the difficulty faced by professors and students at international PhD programs. The students were found to perceive positive attitudes towards the carefully selected instructions design of action research with Flipped-Jigsaw approach. The implications were also proposed. Abstrak: Artikel ini melaporkan refleksi dari salah satu mata kuliah yang saya ambil pada semester ini yaitu Metodologi Penelitian Pendidikan. Untuk menyusun makalah ini, saya menggunakan metode kualitatif biografis-reflektif yang selaras dengan paradigma interpretatif metodologi penelitian inkuiri naratif untuk menggambarkan pengalaman saya sendiri dalam proses pembelajaran. Data yang saya gunakan adalah postingan dari aplikasi mobile Zuvio yang dirancang untuk proses pembelajaran dengan platform online dan pengalaman pribadi dari proses reflektif kursus. Saya menganalisis data dengan tiga tahap analisis data kualitatif: reduksi data, penyajian data, dan penarikan kesimpulan. Temuan penelitian ini menunjukan bahwa kelas yang dilakukan dengan penelitian tindakan kelas telah berhasil mengatasi kesulitan yang dihadapi oleh profesor dan mahasiswa di program PhD internasional. Para siswa merasakan sikap positif terhadap desain instruksi penelitian tindakan yang dipilih dengan cermat dengan pendekatan Flipped-Jigsaw. Implikasinya juga diusulkan pada artikel ini.